Therapeutic effects of higenamine combined with [6]‐gingerol on chronic heart failure induced by doxorubicin via ameliorating mitochondrial function. Issue 7 (19th February 2020) - Wen, Jianxia; Zhang, Lu; Wang, Jian; Wang, Jiabo; Wang, Lifu; Wang, Ruilin; Li, Ruisheng; Liu, Honghong; Wei, Shizhang; Li, Haotian; Zou, Wenjun; Zhao, Yanling
Abstract: Higenamine (HG) is a natural benzylisoquinoline alkaloid isolated from Aconitum with positive inotropic and chronotropic effects. This study aimed to investigate the possible cardioprotective effects of HG combined with [6]‐gingerol (HG/[6]‐GR) against DOX‐induced chronic heart failure (CHF) by comprehensive approaches. DOX‐induced cardiotoxicity model in rats and H9c2 cells was established. Therapeutic effects of HG/[6]‐GR on haemodynamics, serum indices and histopathology of cardiac tissue were analysed. Cell mitochondrial energy phenotype and cell mitochondrial fuel flex were measured by a Seahorse XFp analyser. Moreover, UHPLC‐Q‐TOF/MS was performed to explore the potential metabolites affecting the therapeutic effects and pathological process of CHF. To further investigate the potential mechanism of HG/[6]‐GR, mRNA and protein expression levels of RAAS and LKB1/AMPK/Sirt1‐related pathways were detected. The present data demonstrated that the therapeutic effects of HG/[6]‐GR combination on CHF were presented in ameliorating heart function, down‐regulation serum indices and alleviating histological damage of heart tissue. Besides, HG/[6]‐GR has an effect on increasing cell viability of H9c2 cells, ameliorating DOX‐induced mitochondrial dysfunction and elevating mitochondrial OCR and ECAR value. Metabolomics analyses showed that the therapeutic effect of HG/[6]‐GR combination is mainly associated with the regulation of fatty acid metabolites and energy metabolism pathways. Furthermore, HG/[6]‐GR has an effect on down‐regulating RAAS pathway‐related molecules and up‐regulating LKB1/AMPKα/Sirt1‐related pathway. The present work demonstrates that HG/[6]‐GR prevented DOX‐induced cardiotoxicity via the cardiotonic effect and promoting myocardial energy metabolism through the LKB1/AMPKα/Sirt1 signalling pathway, which promotes mitochondrial energy metabolism and protects against CHF.